The Codification of Islamic History for Sunnis and Shiites: A Critical Reading - Zwain, Qassim Khalaf Salman; Abed Al-Mohammadi, Hussein (Al-Adab Journal, 2022)
It can be said that the trends in reading and writing history for any nation are as many as the multiplicity of goals and partisanship in that nation. The difference is in the consideration and vision of that incident, and then in its analysis and interpretation, but in believing and taking it or denying it and turning away from it. The historical material and how it is read and interpreted is often a source of controversy and contrast between those with different orientations; each - according to human habit and nature - reads history and writes it down in accordance with his belief and doctrine. Our Islamic history was not immune to this, as its readings were numerous and its events varied. According to the trends and whims of historians, and the reflection of prejudices and political and sectarian affiliations on what they wrote in their pens, the result of this was the inability to know our Islamic history as it was, and only a confused and turbulent history reached us. It hardly withstands criticism and examination, and does not resist excavation and research. It tells and tells about the biography of everyone who rose to the throne and the caliphate, and everyone who ruled in the name of the Messenger of God, may God bless him and his family, regardless of his intentions and goals. The original missionary line represented by the divine leaders who were appointed by the Messenger of God, may God bless him and his family, to preserve the message and preserve it from distortion, and who were unique in writing Islamic history on its origins, without falsity and distortion, nor fabrication and distortion, despite the ruling authorities’ ban on writing, and the pressure they were exerting on the Companions and followers. It can be said that the Islamic trends in the writing of history, including: what was consumed by time and drank, and among them: what merged and fused into others, and in light of this, there are only two main different trends left in reading and writing history, each with its own style and approach, and its adoptions and constants . The first tendency of Ahl al-Sunnah wal-Jama’ah, or the school of governance and caliphate, where they proceeded from the idea that the Companions represent the only source and mediator that connects them with the Noble Prophet, may God’s prayers and peace be upon him and his family, so they judged the justice of all the Companions, and the necessity of taking from them without research and investigation, and the impermissibility of wounding and modifying in Their right, nor the question of their justice, but rather it is a foregone conclusion. The second trend is for the followers of the Ahl al-Bayt school, peace be upon them, who believed that the imams of Ahl al-Bayt, peace be upon them, were appointed by Almighty God after the Noble Prophet, may God’s prayers and peace be upon him and his family, and that they should be followed, taken from them, and prioritized over all the Companions without exception. There is a third trend represented by orientalists, which has repercussions that may be dangerous in some aspects on the presentation of Islamic history and its narration. It has nothing to do with the Muslims’ view of the purpose and goal of writing Islamic history, but rather they have their own motives, goals and objectives. We will focus in this research on the specific rules that had an impact and effectiveness in classifying Muslim historians into these two directions; The direction of Ahl al-Sunnah wal-Jama`ah and the direction of the followers of Ahl al-Bayt, peace be upon them; This is because the general rules for writing general history and Islamic history in particular are often common rules; There is no disagreement about it except in some details and interpretations adopted by this trend or that.